Determination of testosterone esters in the hair of male greyhound dogs using liquid chromatography–high resolution mass spectrometry. Issue 3 (23rd August 2017) - Devi, Jayasree Leela; Zahra, Paul; Vine, John H.; Whittem, Ted
Abstract : The doping of greyhound dogs with testosterone is done in an attempt to improve their athletic performance, but such doping cannot easily be confirmed, especially in male dogs owing to the natural presence of endogenous testosterone. As testosterone is usually administered as its esters, their direct detection in hair would provide confirmatory evidence of the administration of a pharmaceutical product. This article demonstrates that the use of a liquid chromatography–high resolution mass spectrometry method with heated electrospray ionisation (HESI) combined with the use of amino solid‐phase extraction (SPE) cartridges for sample clean‐up, is suitable for the sensitive determination of propionate, phenyl propionate, isocaproate, decanoate, and enanthate esters of testosterone in greyhound hair. The method is linear over the range, 0.1 μg/kg–10 μg/kg, for all the testosterone esters analysed. The limits of detection (LOD) are 0.05 μg/kg for testosterone phenyl propionate, isocaproate, and decanoate, 0.025 μg/kg for testosterone propionate, and 0.25 μg/kg for testosterone enanthate. This method was applied to hair samples collected from male greyhounds before and after a single administration of a product containing several testosterone esters, each of which could be detected up to 100 days post‐administration. The study also demonstrates that tail hair is the specimen of choice for the analysis of testosterone in dog hair and that washing of dogs does not impact the analysis of testosterone esters in hair. This method may be useful in racing regulation for the detection of illegitimate use of testosterone in all species. Abstract : The study demonstrates that the use of a liquid chromatography‐high resolution mass spectrometry method with heated electrospray ionisation (HESI) combined with the use of amino SPE cartridges for sample clean up, improves the selectivity and sensitivity of the method for the determination of propionate, phenyl propionate, isocaproate, decanoate and enanthate esters of testosterone in greyhound hair. This method was applied to hair samples collected from male greyhounds before and after a single administration of a product containing several testosterone esters each of which could be detected up to 100 days post‐administration.